2010
DOI: 10.3390/ijms11010312
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Structurally-Related Compounds Protect Synaptosomal Membranes from Free Radical Damage

Abstract: Since biological membranes are composed of lipids and proteins we tested the in vitro antioxidant properties of several indoleamines from the tryptophan metabolic pathway in the pineal gland against oxidative damage to lipids and proteins of synaptosomes isolated from the rat brain. Free radicals were generated by incubation with 0.1 mM FeCl3, and 0.1 mM ascorbic acid. Levels of malondialdehyde (MDA) plus 4-hydroxyalkenal (4-HDA), and carbonyl content in the proteins were measured as indices of oxidative damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…NecroX administered in vivo and in vitro possibly resides in the mitochondrial matrix and then scavenges mitochondrial ROS such as superoxide, hydrogen peroxide, and peroxynitrite during cellular damage. Our results are consistent with previous studies showing that chemical compounds containing a key moiety of indole ring, such as melatonin, have antioxidant activity in in vitro (Poeggeler et al, 1996;Millán-Plano et al, 2010) and in vivo models (Jaworek et al, 2003) through attenuation of mitochondrial dysfunction (Acuna-Castroviejo et al, 2007;Escames et al, 2007). Further studies are needed to verify the antioxidant behavior of NecroX in terms of target site, intracellular localization, tissue distribution, and electron spin resonance (ESR) study.…”
Section: Discussionsupporting
confidence: 94%
“…NecroX administered in vivo and in vitro possibly resides in the mitochondrial matrix and then scavenges mitochondrial ROS such as superoxide, hydrogen peroxide, and peroxynitrite during cellular damage. Our results are consistent with previous studies showing that chemical compounds containing a key moiety of indole ring, such as melatonin, have antioxidant activity in in vitro (Poeggeler et al, 1996;Millán-Plano et al, 2010) and in vivo models (Jaworek et al, 2003) through attenuation of mitochondrial dysfunction (Acuna-Castroviejo et al, 2007;Escames et al, 2007). Further studies are needed to verify the antioxidant behavior of NecroX in terms of target site, intracellular localization, tissue distribution, and electron spin resonance (ESR) study.…”
Section: Discussionsupporting
confidence: 94%
“…2). This latter compound seems to have beneficial effects in preventing both lipid and protein oxidation in synaptosomal membranes (Millán-Plano et al, 2010). Thus, methoxy and acyl groups are essential substituents for the antioxidant properties of melatonin.…”
Section: Melatonin As An Antioxidant Defense Systemmentioning
confidence: 99%
“…Another study states that Wistar albino rats administered with drinking water and aluminum chloride had edema and tissue disintegration in their brain, and showed that vitamin E and C given as antioxidants reduced the damage that occurred (Hussein et al, 2010). Mel is one of the most powerful antioxidants, terminating lipid peroxidation, by capturing peroxyl radicals (Karbownik and Reiter, 2000;Li et al, 2008;Millan-Plano et al, 2010). Mel shows an antioxidant effect in the presence of metals causing oxidative stress, thereby reducing the damage occurring or eliminating it altogether Sharma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%